The correlation between vitamin B12 and folate levels and bone mineral density among the Saudi population in a primary care setting - Sarah I Bin Hussain; Abdullah AlKhenizan; Ahmed Mahmoud; Hussain Qashlaq (Journal of Family Medicine and Primary Care)
Purpose: Bone health and osteoporosis are significant health problems in Saudi Arabia. Approximately 40%–50% of women and 25%–33% of men sustain osteoporotic fractures in their lifetimes. Hence, identifying the risk factors for osteoporosis is crucial in reducing the incidence of fractures. Materials and Methods: We retrospectively reviewed the electronic medical records of 557 patients (female 60%, male 40%) aged ≥18 years (mean age, 66.53 years [standard deviation ± 14.169]) who underwent bone mineral density (BMD) scans at the Department of Family Medicine & Polyclinics, King Faisal Specialist Hospital and Research Centre (KFSH&RC) between January 2004 and June 2019. Data collected included demographics, BMD values, vitamin B12 levels, and folate levels. Results: This study indicated that the prevalence rates of vitamin B12 and folate deficiencies among the study population were 8.4% and 1.3%, respectively. There was a statistically significant association between vitamin B12 levels and fracture risk (P =0.044). However, no statistically significant correlation was observed between BMD at either site (lumbar spine or femoral neck) and vitamin B12 (P =0.926.,070) and folate levels (P =.683.,79). BMD showed a significant positive correlation with body mass index at the lumbar spine and femoral neck (P = 0.000). There was no statistically significant association between vitamin B12 levels and the use of metformin (P =.26). Conclusion: Vitamin B12 is associated with fracture risk; however, vitamin B12 and folate levels are not correlated to BMD (femoral neck and lumbar spine).